Gross anatomical study on the Sternum of Jungle Babbler (Argya striata) - Rupam Sinha,; Archana Pathak,; Anand Singh,; Abhinov Verma,; Shri Prakash Singh, (Indian Journal of Veterinary Anatomy, 2024)
Study was conducted on sternum of a Jungle Babbler to record its gross morphological features. The sternum of Jungle Babbler was small boat shaped single bone located at antero-ventral aspect the body cavity. The cranial border was broad. The dorsal surface was concave. The ventral surface was more convex, rough and continued with keel bone. Cranio-lateral process was directed upward. Metasternum was thin and triangular in shape. Unlike other flight birds postero-lateral process was found with thoracic process. Five pairs of coastal articular facets were present between processus thoracic and caudolateral process on either side for the attachment of sternal ribs. Facet for articulation with distal end of coracoid bone was found between the cranio- lateral process and processus thoracic.